2013
DOI: 10.1186/1472-6831-13-7
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Dental caries among children 7–14 years old in Northwest Ethiopia: a community based cross-sectional study

Abstract: BackgroundDental caries in children remains a significant public health problem. It is a disease with multifactorial causes. The aim of the study was to assess the prevalence and associated factors of dental caries among children between 7 to 14 years old.MethodsA community based cross-sectional study was conducted in Gondar town from June 2011 to September 2011. A total of 842 children were involved in the study. Multi-stage sampling technique was used to select the children. Pretested and structured question… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
72
1
9

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(98 citation statements)
references
References 9 publications
16
72
1
9
Order By: Relevance
“…The study done in Gondar showed that there was a statistically significant association between dental caries and educational status (AOR = 0.37, 95% CI, 0.17, 0.80). Dental caries among children whose father were above grade 12 were 63% times at a lower risk compared to illiterates [19]. …”
Section: Introductionmentioning
confidence: 99%
“…The study done in Gondar showed that there was a statistically significant association between dental caries and educational status (AOR = 0.37, 95% CI, 0.17, 0.80). Dental caries among children whose father were above grade 12 were 63% times at a lower risk compared to illiterates [19]. …”
Section: Introductionmentioning
confidence: 99%
“…In Ethiopia, prevention and treatment of oral health related illness had little attention; although oral health related illness is affecting majority of the Ethiopian, much is not known about the extents and factors associated with oral health related illnesses and oral care practices and health care seeking behavior in most parts of the country including in Addis Ababa [10,11]. Therefore, this study sought to estimate the prevalence of oral health related illness and its associated factors among bank employees and teachers in Addis Ababa.…”
Section: Introductionmentioning
confidence: 99%
“…26 Başka bir çalışmada ise, diş sağlığı ile ilgili alışkanlıkların yerleşmesinde velilerin davranışlarının çocuklarını doğrudan etkilediği, çocuğun ailesi ile geçirdiği kaliteli zamanın bu alışkanlıklarda önem taşıdığı bildirilmiş, ailenin bilinç ve eğitim düzeyinin çocuğun çürük insidansı ile ilişkili olduğu öne sürülmüştür. [27][28][29][30] Mevcut çalışmada anne ve babaların öğrenim seviyeleri genel olarak düşüktür. Anket verilerine göre annelerin %60,9'u ilkokul, %10,2'si ortaokul, %9,4'ü lise, %4,7'si üniversite mezunu iken, %14'ü okuryazar değildir.…”
Section: Discussionunclassified